Opinions of Montenegrin University Students and Teachers about Plagiarism and its Prevention - Dijana Vučković; Sanja Peković; Rajka Đoković; Marijana Blečić; Jovana Janinović (Center for Educational Policy Studies Journal)
This research paper aims to identify the opinions of university students and teachers about plagiarism and how to prevent it. We employed qualitative techniques, providing three case studies to participants and asking open-ended questions based on these cases. One hundred and forty-five people participated in this study, including bachelor, master, and doctoral students and university teachers. We performed a thematic analysis of the text received from the participants’ responses. The results show that the participants were serious about plagiarism if academic stakeholders commit it; however, they expressed a lenient attitude toward ghostwriters. They also felt there was a need to provide training in academic writing for them to feel confident about their writing and not copy from others. Some awareness sessions on academic integrity should also be conducted.